(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The education that we grant today focuses much on the cognitive (head) angle and we only occasionally offer significance to the emotional (heart) perspective. It has been accepted by all that education should assist the person with solving the difficulties of life and make successful adjustment throughout everyday life. All people have emotions and general intelligence inside themselves however what number of individuals carries on as indicated by the correct Emotions and Intelligence in their life? The purpose of education ought not to be to just give sustenance to the cerebrum yet it ought to recharge the heart too. Swami Vivekananda had properly pointed out, It’s the heart which takes one to the highest spot where intellect can never reach. In such manner, an endeavor has been made to consider the relationship of emotional intelligence with adjustment, stress and achievement among Senior Secondary School Students. Emotional Intelligence and Academic Achievement, which exhibits that as the emotional intelligence builds the scholastic achievement furthermore increments and the other way around. This examination additionally demonstrates the negative correlation between the following variables- Emotional Intelligence and Stress (Academic stress and Family stress), Emotional Intelligence and Adjustment (Home, Health, Social and Emotional), which demonstrates that the students who have high emotional intelligence have low level of stress and better adjustment in their life which is particularly valuable for making progress throughout everyday life.